Globalisation and trade unions: towards a multi-level strategy?. (1st April 2008) - Ronaldo Munck
Abstract : International trade unionism is facing a serious challenge from what is commonly called globalisation. Trade unions feel the need to 'scale up' their activities beyond their, once paramount, national terrain and to challenge capital's untrammelled forward march internationalising and commodifying everything in its path. This article examines the new forms of labour internationalism and the way in which trade unions have been creating incipient counter-hegemonic strategies. The only certainty in this globalised and complex situation is that a continuation of national era trade union strategies is not a viable path. A possible 'transformationalist' alternative is posed in this paper, arguing that labour needs a multi-layered and flexible response to the new global capitalist order.